THE REFLECTION OF ATTITUDE CHANGE IN ANTON CHEKOV’S STORY “FAT AND THIN” - Arianto, Tomi; Septriani, Septriani (Asosiasi Ide Bahasa Kepri, 2023)
This study aim to reveal the attitude change that are reflected through the story character written by Anton Chekov entitled “Fat and Thin”. Anton Chekov with his high-level imaginative mind can use narration in criticizing human behavior, especially the vertical nature of Russian society which likes to serve itself in positions and titles which are also known as